2014
DOI: 10.1097/iae.0b013e318295f701
|View full text |Cite
|
Sign up to set email alerts
|

Subretinal Drusenoid Deposits With Increased Autofluorescence in Eyes With Reticular Pseudodrusen

Abstract: Subretinal drusenoid deposits are not homogeneous and can be classified into two types according to the fundus autofluorescence. Multimodal imaging tests are needed for the differential diagnosis of subretinal drusenoid deposits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 24 publications
2
30
1
Order By: Relevance
“…Nomenclature: In previous studies, the terms reticular pseudodrusen, pseudo-reticular drusen, or pseudodrusen was used for different en face modalities 2, 8, 15, 2532 , and the term subretinal drusenoid deposits for cross-sectional histology and SD-OCT 6, 7, 32, 33 In the present article, we will use the term pseudodrusen for standard en face ophthalmoscopy (color fundus photography, infrared reflectance (IR), red-free (RF), and autofluorescence (AF)) and the term subretinal drusenoid deposits for the collections of material seen in the subretinal space in histologic specimens, AOSLO, and OCT.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nomenclature: In previous studies, the terms reticular pseudodrusen, pseudo-reticular drusen, or pseudodrusen was used for different en face modalities 2, 8, 15, 2532 , and the term subretinal drusenoid deposits for cross-sectional histology and SD-OCT 6, 7, 32, 33 In the present article, we will use the term pseudodrusen for standard en face ophthalmoscopy (color fundus photography, infrared reflectance (IR), red-free (RF), and autofluorescence (AF)) and the term subretinal drusenoid deposits for the collections of material seen in the subretinal space in histologic specimens, AOSLO, and OCT.…”
Section: Methodsmentioning
confidence: 99%
“…30 It is recommended that detection should be confirmed using more than one modality for improving accuracy. 30, 31 The identification of pseudodrusen in our study was based on their presence in at least 2 en face imaging modalities and in SD-OCT. 27, 29, 32 In en face imaging, pseudodrusen appear as an interlacing collection of ribbons or a dot-like pattern of yellow-white lesions (in color fundus photography), a pattern of hypo-reflective or hyper-reflective spots (in IR reflectance), or a pattern of small hypo-autofluorescent areas against a background of mild hyper-autofluorescence (in AF). Although a reticular pattern was often seen in color photography, it was not a criterion for diagnosis.…”
Section: Methodsmentioning
confidence: 99%
“…The hypoautofluorescent nature of these lesions additionally suggests that they are not directly derived from photoreceptor outer segments as these would be highly autofluorescent due to abundant bisretinoid. Recently, Lee and Ham have identified a minority of RPD that display hyperautofluorescence, which suggests that these deposits additionally contain retinoid components either from the photoreceptor, or lipofuscin from the RPE (Lee and Ham, 2014). They conclude by suggesting that RPD may fall into at least two types, classical hypoautofluorescent RPD and a hyperautofluorescent variant (Lee and Ham, 2014).…”
Section: Fundus Autofluorescence Of Reticular Pseudodrusenmentioning
confidence: 99%
“…8,9 Among them, Suzuki et al 8 introduced a classification of reticular pseudodrusen into three different subtypes on the basis of morphologic features: dot pseudodrusen, ribbon pseudodrusen, and peripheral pseudodrusen. In their study, dot, ribbon, and peripheral pseudodrusen were found in 96.1%, 40.2%, and 5.7% of eyes with pseudodrusen, respectively.…”
mentioning
confidence: 99%